Waqf microfinance as an alternative and sustainable government empowerment tool towards women in Northern Nigeria: a perceptional analysis - Muhammad, Tijjani; Al-Shaghdari, Fahd Mohammed Obad (Emerald Publishing Limited, 2025)
Purpose – The study investigates the perception of Northern Nigeria’s women toward addressing unemployment and enhancing microeconomic activities using the uniquely proposed Waqf microfinance model. Design/methodology/approach – This quantitative study relies on analytical techniques using random and probability sampling strategies. Based on their geographical distribution and business sector diversity, the study selected 346 businesswomen and customers participating in local businesses in Northern Nigeria. Structural equation modeling (SEM) and confirmatory factor analysis (CFA) were used for the analyses. Findings – The study indicates a strong relationship between Waqf microfinance and women’s empowerment in promoting women’s sustainable development. Therefore, the study suggests using Waqf microfinance frameworks towards an endowment to empower women’s microeconomic activities in Northern Nigeria. The findings also justify the direct and indirect effects of the relationship in promoting sustainable schemes for women’s empowerment in Nigeria. Further, it indicates the potential for a women’s empowerment scheme using Waqf’s microfinance based on SEM. Practical implications – The study sheds light on the potential of Waqf microfinance as a tool for developing microeconomics through women’s empowerment in Northern Nigeria. Originality/value – This study marks a significant milestone in the field. It is the first to explore the perception of Waqf microfinance as a viable choice for women’s empowerment.